Role of intermediate layer for La2/3Sr1/3MnO3/SiO2/Si(100) granular thin films - Shim, IB; Kim, CS; Park, KT; Oh, YJ (ELSEVIER SCIENCE BV, 2001)
Magnetotransport properties of La2/3Sr1/3MnO3 (LSMO) (1500 Angstrom)/YSZ (100-1500 Angstrom)/SiO2/Si (100) bilayers were investigated by low-field magnetotransport measurement at room temperature. It is observed that MR ratio of the films with a YSZ buffer layer (MR = 0.43 %) was much higher than those of the films without a buffer layer (MR = 0.21 %) The better results of the LSMO films with a YSZ diffusion barrier are deduced to be related to the improvement of microstructure of the films and the reduction of the interface reaction between the films and SiO2/Si (100) substrates. (C) 2001 Elsevier Science B.V. All rights reserved.
Keywords: MANGANITES